ANALISIS NILAI BUDAYA DAN FUNGSI “TRADISI MANTEN MUBENG GAPURA” DI MASJID WALI AT-TAQWA LORAM KULON KUDUS (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Research on the analysis of "Values ​​and Functions of Tradision Manten Mubeng Gapura at mosque Wali At-Taqwa Loram Kulon Kudus" was conducted in Loram Kulon Village, Jati District, Kudus Regency, Central Java. This study uses a qualitative descrptif approach. Data collection techniques through literature, observation, interviews, recording, writing and taking pictures. The results of this study obtained the values ​​and functions of the manten mubeng gapura padureksan tradition, the values ​​associated with this tradition are religious values ​​and cultural values ​​while its function is as a medium of da'wah and to introduce if a Muslim must have a sense of responsibility and not leave obligations.